2016
DOI: 10.1074/jbc.m115.706135
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Nef-associated Factor 1 Enhances Viral Production by Interacting with CRM1 to Promote Nuclear Export of Unspliced HIV-1 gag mRNA

Abstract: HIV-1 depends on host-cell-encoded factors to complete its life cycle. A comprehensive understanding of how HIV-1 manipulates host machineries during viral infection can facilitate the identification of host targets for antiviral drugs or gene therapy. The cellular protein Naf1 (HIV-1 Nef-associated factor 1) is a CRM1-dependent nucleo-cytoplasmic shuttling protein, and has been identified to regulate multiple receptor-mediated signal pathways in inflammation. The cytoplasm-located Naf1 can inhibit NF-B activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
(77 reference statements)
1
9
0
Order By: Relevance
“…Naf1 has been reported to be a shuttling protein that moves between the cytoplasm and the nucleus (17,20). The cytoplasmic and nuclear localization of Naf1 was confirmed by confocal microscopy (Fig.…”
Section: Naf1 Suppresses Hiv-1 Long Terminal Repeat (Ltr)-driven Genementioning
confidence: 58%
See 4 more Smart Citations
“…Naf1 has been reported to be a shuttling protein that moves between the cytoplasm and the nucleus (17,20). The cytoplasmic and nuclear localization of Naf1 was confirmed by confocal microscopy (Fig.…”
Section: Naf1 Suppresses Hiv-1 Long Terminal Repeat (Ltr)-driven Genementioning
confidence: 58%
“…These data may suggest that Naf1 possesses multifaceted and likely cell-type-dependent roles in regulating HIV-1 infection. Naf1 has been shown to be a nucleocytoplasmic shuttling protein (17,20). Recently, we found that nuclear Naf1 could promote nuclear export of unspliced HIV-1 gag mRNA, leading to increased Gag production for viral assembly and release (20).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations